Climate and Climate Variability in the Arenal River Basin of Costa Rica - Amador Astúa, Jorge Alberto (2003)
This work examines some of the effects of climate and climate variability in the Arenal River basin of Costa Rica, the site of the largest hydropower complex in the country. The Arenal system, which drains part of the north-central portion of Costa Rica covers a total area of approximately 493 km2 ; it is mainly managed for electric power generation and produces nearly a quarter of the total annual electricity in Costa Rica. Monthly, pentad (5-day means), and daily precipitation data are used to study signals associated with climate and shorter-term atmospheric disruptions in the basin. Although the study area is relatively small, strong spatial and temporal contrasts of precipitation patterns are found. A clear distinction in the seasonal distribution of precipitation is observed over short distances (~30–40 km), between the northwestern (NW) low lands of the basin compared to the southeastern (SE) sector. The former region exhibits a bimodal precipitation distribution, with maxima in June and September–October, and relative minima in July and December–April. The July minimum suggests a weak mid-summer drought or “veranillo” signal. The latter region has practically no dry season with the highest precipitation values occurring during the second part of the calendar year. As determined by principal component analysis of anomalies of monthly precipitation data, the main disruption of the normal pattern of precipitation appears to be related to the ENSO signal in the NW region, whereas the SE sector shows a positive correlation with Caribbean low-level wind changes. Some of the latter changes are associated with warm or cold ENSO episodes that seem to modulate wind intensities of the low-level jet over the Caribbean. Precipitation effects in the basin for selected extreme cases, such as that of hurricane Mitch, and other so-called “temporales” are also analyzed. The importance of these systems as fundamental components of the basin’s hydrological cycle is well established. ENSO related variability of the regional summer circulation (such as that of the low-level jet in the western Caribbean), and the appearance of cases of extreme strong trade winds during the winter circulation are also important forcing mechanisms for precipitation variability in the basin. In these cases, the interaction between the basin complex topography, and changes in the flow pattern and intensity seem to be of fundamental importance for precipitation variance. Some socioeconomic impacts of precipitation variability, as well as a discussion about the potential use of climate variability information for water management in the basin are presented